Identification of Marine Neuroactive Molecules in Behaviour-Based Screens in the Larval Zebrafish - Si-Mei Long (Marine Drugs, 2014)
High-throughput behavior-based screen in zebrafish is a powerful approach for the discovery of novel neuroactive small molecules for treatment of nervous system diseases such as epilepsy. To identify neuroactive small molecules, we first screened 36 compounds (1–36) derived from marine natural products xyloketals and marine isoprenyl phenyl ether obtained from the mangrove fungus. Compound 1 demonstrated the most potent inhibition on the locomotor activity in larval zebrafish. Compounds 37–42 were further synthesized and their potential anti-epilepsy action was then examined in a PTZ-induced epilepsy model in zebrafish. Compound 1 and compounds 39, 40 and 41 could significantly attenuate PTZ-induced locomotor hyperactivity and elevation of c-fos mRNA in larval zebrafish. Compound 40 showed the most potent inhibitory action against PTZ-induced hyperactivity. The structure-activity analysis showed that the OH group at 12-position played a critical role and the substituents at the 13-position were well tolerated in the inhibitory activity of xyloketal derivatives. Thus, these derivatives may provide some novel drug candidates for the treatment of epilepsy.